Razveljavitev in odprava prostorskih načrtov v luči novele ZUreP-3C in odločitev Ustavnega sodišča RS - Kvenderc, Tit (Pravnik, 2025)
The article addresses the issue of land-use designation changes and the legal remedies available against spatial planning acts that determine such designations. In Decision U-I-474/22 of 20 March 2025, the Constitutional Court ruled that Article 61 of the Slovenian Spatial Management Act (ZUreP-3) is unconstitutional, as it grants the Administrative Court jurisdiction to annul general acts—an authority that, under Article 160 of the Constitution, belongs exclusively to the Constitutional Court. At the same time, the Court emphasised that the situation requiring it to adjudicate on spatial acts itself is also unconstitutional—specifically due to the requirements of EU law and the need for effective judicial protection. Despite its unconstitutionality, Article 61 was left temporarily in force, with the legislature instructed to resolve the issue. In September 2025, the National Assembly adopted a major amendment (ZUreP- 3C), revising more than one-third of the provisions of the Act. However, despite warnings from the Legislative Service of the National Assembly, it failed to address the identified unconstitutionality. As this concerns a systemic issue of jurisdictional allocation, a constitutional amendment may even be on the horizon, explicitly granting the Administrative Court the power to annul implementing spatial acts.
Keywords: Constitutional Court; državni zbor; land-use designation; legal interest; municipal spatial plan; namembnost zemljišč; National Assembly; OPN; pravni interes; prostorski akt; spatial planning act; ustavno sodišče; ZUreP-3